Dietary Protein Intake throughout Childhood Is Associated with the Timing of Puberty - Günther, Anke L. B.; Karaolis-Danckert, Nadina; Kroke, Anja; Remer, Thomas; Buyken, Anette (The Journal of Nutrition)

Compositional CSP Traces Refinement Checking - Wehrheim, Heike; Wonisch, Daniel (Electr. Notes Theor. Comput. Sci.)

Static Class Elements for Object-Z - Ruhroth, Thomas; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Measure, Diagnose, Refactor: A Formal Quality Cycle for Software Models - Ruhroth, Thomas; Voigt, Hendrik; Wehrheim, Heike (35th Euromicro Conference on Software Engineering and Advanced Applications, SEAA 2009, Patras, Greece, August 27-29, 2009, Proceedings)

Integrated Formal Methods, 7th International Conference, IFM 2009, Düsseldorf, Germany, February 16-19, 2009. Proceedings

Productivity management for customer solutions --- Towards a performance management system for efficient service value networks - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Knackstedt, Ralf; Nüttgens, Markus; Thomas, Oliver; Fellmann, Michael (29th International RESER Conference)

Configurative Service Engineering --- A Rule-Based Configuration Approach for Versatile Service Processes in Corrective Maintenance - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin (Proceedings of the 42th Hawaii International Conference on System Sciences)

A Framework for Design Research in the Service Science Discipline - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (Americas Conference on Information Systems)

Design Requirements to Support Information Flows for Providing Customer Solutions: A Case Study in the Mechanical Engineering Sector - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver (Proceedings of the First International Symposium on Services Science (ISSS'09))

Model-Based Decision Support for the Customer-Specific Configuration of Value Bundles - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Enterprise Modelling and Information Systems Architectures)

Professional learning and TVET: challenges and perspectives for teachers and instructors - Harteis, Christian (International handbook of education for the changing World of Work)

Lernen von Lehrenden im Arbeitsprozess - Mulder, Regina H; Harteis, Christian; Gruber, Hans (Lehrprofessionalität - Bedingungen, Genese, Wirkungen und Messung)

Mikroanalytische Begleitung der Steuerpolitik am Beispiel der Erbschaftsteuerreform - Maiterth, Ralf; Houben, Henriette; Broekelschen, Wiebke; Müller, Jens; Sureth-Sloane, Caren (Statistik und Wissenschaft)
Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation | Deutschland | Germany
Keywords: Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation

Wirtschaft und Betrieb - Heid, Helmut; Harteis, Christian (Handbuch Bildungsforschung)

Hierarchisches Clustering mit minimalen Cluster-Durchmessern - Schröer, Carsten

Teacher Collaboration Concerning ICT-Use and its Essential Conditions - Schulz-Zander, Renate; Eickelmann, Birgit (Proceedings – 9th WCCE. IFIP World Conference on Computers in Education)

E-teaching plus. Die webbasierte Lernumgebung für situiertes Lernen mit Unterrichtsvideos - Schulz-Zander, Renate; Eickelmann, Birgit

National Policies and Practices on ICT in Education: Germany - Schulz-Zander, Renate; Eickelmann, Birgit (Cross-national Information and Communication Technology. Policies and Practices in Education)

Analyse und Evaluation eines identitätsbasierten Signcryption-Verfahrens - Liske, Gennadij

Die Schwierigkeit des k-Median Clusterings für Bregman-Divergenzen - Scholz, Christoph